ANALISIS KINERJA DAN ADMINISTRASI PAJAK DAERAH DI KABUPATEN BOGOR - Deden Muhammad Haris (Universitas Sultan Ageng Tirtayasa, 2010)
The research regarding revenue analysis and local tax administration in Bogor Regency has purpose to gain more tax revenue obtained by Bogor Regency and to know the implementation of tax administration in managing local tax performed by The Income Service of Bogor Regency. The Local taxes analyzed are Hotel and Restaurant Tax, Entertainment Tax, Advertising Tax, Street Lighting Tax, and Mineral Removal and Processing Tax. Analysis of tax revenue was carried out by : first, analyzing local tax performance. second, to know the implementation of local tax administration is by studying tax administratively namely instituion, employees and activities. Analytical result of local tax performance that consist of Tax Effort, Tax Effectiveness and Tax Efficiency. Tax Effort consist of Tax Elasticity which its value is 0.1% and Tax Ratio that its range value from 0.14% untill 41%. Another peformance local tax is Tax Effectiveness that its range value from 1.01 untill 1.16 and Tax Efficiency that its range value is from 20.36% untill 22.49%. The analytical result of the implemntation of local tax administration is as follows : first, there is no job description at each section and subsection. Second, lack of quantity and quality of employees. It lacks of coordination of education and training that are tax and accounting base. Third, lack of coordination with other institution in collecting data and registration. The writer suggest that the local income service office explore more tax revenue by carrying out local tax intensification by enlarging revenur basis, strengthening levy process, improving supervison, improving administrative effectiveness.